Evaluation of microemulsions containing a large amount of a deep eutectic solvent as a potential transdermal carrier of resveratrol - Sakuragi, M. (IOP Publishing Ltd, 2020)
Inclusion of a large amount of deep eutectic solvent (DES) in a microemulsion (ME) may enhance transdermal permeation of resveratrol (RSV) due to its high solubility in DES of the inner phase. We prepared MEs with different DES loading and surfactant composition, and investigated the entrapment amount of RSV, the structures of the MEs, and their skin penetration amount. We found that MEs at Tween-80/Span-20 = 4/1 (wt/wt) (T4S1) were able to contain the largest amount of DES in the inner phase. The structural characterization results showed that T4S1-MEs containing more than 20 wt DES and less than 10 wt DES formed a vesicle containing DES in the membrane of surfactants and a spherical micelle containing DES in the inner phase, respectively. The vesicles containing more than 20 wt DES were able to trap a larger amount of RSV and deliver more RSV through the stratum corneum compared to the spherical micelles containing less than 10 wt DES. Â© 2020 The Japan Society of Applied Physics.